Microstructure of advanced tool steels produced by powder metallurgy - Serak, Jan; Pecinka, Vojtech; Vojtech, Dalibor (Manufacturing Technology Journal, 2018)
In this work, the microstructure and mechanical properties of three types of high-speed tool steels (Vanadis 60, ASP 2052 and S 705) were studied. The steel S 705 was made by conventional ingot metallurgy technology, and other types of steels were manufactured by powder metallurgy technology. The studied steels were examined both in the soft state and further in the hardened condition with subsequent tempering. Microstructure of metallographic cuts and fracture areas was studied by electron microscopy. Hardness, tensile properties and notch toughness were determined. Significant differences in the properties of steels in both studied states have been documented.
Keywords: high-speed steels; microstructure; mechanical properties